Framing the Study of Transnational Families in Lithuania - Juozeliūnienė, Irena (Vilnius University Open Series, 2020)
This chapter aims to place the study of Lithuanian transnational families within a broader body of the most recent theoretical frames through which to understand personal lives, family practices and the ways family relationships could be perceived as ‘troubled’. The author provides a short overview of theoretical approaches and research methodologies used at the Department of Sociology at Vilnius University since 2004 to frame the study of transnational families in Lithuania.